2018
DOI: 10.1002/mus.26195
|View full text |Cite
|
Sign up to set email alerts
|

Altered bone‐regulating myokine expression in skeletal muscle Of Duchenne muscular dystrophy mouse models

Abstract: Dystrophic skeletal muscle demonstrated a significantly altered myokine gene expression profile. mRNA and protein levels of several bone-regulating myokines were significantly altered in dystrophic skeletal muscle, which suggests pathological role of bone-regulating myokines on bone homeostasis in DMD. Muscle Nerve 58: 573-582, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 74 publications
2
34
0
Order By: Relevance
“…It has been reported that besides the liver, which is the main FGF‐21 secretory organ, FGF‐21 can also be secreted by adipose tissue and skeletal muscle . We have recently shown that FGF‐21 mRNA and protein expressions are dramatically upregulated in dystrophic skeletal muscles . To further identify the origin of the elevated circulating FGF‐21 in dystrophic mice, we compared the levels of protein and transcript abundance of FGF‐21 in liver, WAT, and skeletal muscles (TA and diaphragm) in WT and dystrophic mice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that besides the liver, which is the main FGF‐21 secretory organ, FGF‐21 can also be secreted by adipose tissue and skeletal muscle . We have recently shown that FGF‐21 mRNA and protein expressions are dramatically upregulated in dystrophic skeletal muscles . To further identify the origin of the elevated circulating FGF‐21 in dystrophic mice, we compared the levels of protein and transcript abundance of FGF‐21 in liver, WAT, and skeletal muscles (TA and diaphragm) in WT and dystrophic mice.…”
Section: Resultsmentioning
confidence: 99%
“…Primer sequences used in this study are listed in Supplementary Table 1. Eukaryotic translation elongation factor 2 (eEF2) was used as an endogenous invariant control for data normalization . Target gene expression, normalized to eEF2, was determined using ∆∆Ct mathematical model normalized to the expression in controls.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…S2). However, inflammatory factors released from dystrophic muscle that have been reported to stimulate osteoclastogenesis such as IL‐6 , IL‐1β , and Fgf21 were all inhibited by growth hormone treatment. Further investigation is needed to determine if the suppression of mRNA encoding these three factors and possibly others contributes to changes in bone resorption by growth hormone.…”
Section: Discussionmentioning
confidence: 97%